2012
DOI: 10.1111/j.1468-2354.2012.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Tough Love and Intergenerational Altruism*

Abstract: This article develops and studies a tough love model of intergenerational altruism. We model tough love by modifying the Barro‐Becker standard altruism model in two ways. First, the child’s discount factor is endogenously determined, so lower childhood consumption leads to a higher discount factor later in life. Second, the parent evaluates the child’s lifetime utility with a constant high discount factor. Our model predicts that parental transfers will fall when the child’s discount factor falls. This is in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…First, it is shown that when the child's habit parameter exogenously shifts upward, the altruistic parent reduces the unexpectedly low income transfer further, so as to mitigate the child's over-consumption. The result is comparable with parental "tough love" behavior that Bhatt and Ogaki (2012) derive, by specifying an endogenous time-discounting function. They show that an altruistic parent reduces income transfer in order to affect the child's rate of patience.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…First, it is shown that when the child's habit parameter exogenously shifts upward, the altruistic parent reduces the unexpectedly low income transfer further, so as to mitigate the child's over-consumption. The result is comparable with parental "tough love" behavior that Bhatt and Ogaki (2012) derive, by specifying an endogenous time-discounting function. They show that an altruistic parent reduces income transfer in order to affect the child's rate of patience.…”
Section: Introductionsupporting
confidence: 56%
“…Second, our tough love is welfare-enhancing to the child if his parent is sufficiently altruistic and relatively rich. This contrasts with the Bhatt and Ogaki model, wherein a mother's tough love reduces her son's welfare, because the mother evaluates her son's future utility by using a different time preference than the child (Bhatt and Ogaki 2012). 4 Second, we discuss how the main results change in the case of "good" habits, in which parents' transfer involves children's good-habit formation that raises their future gratification (e.g., transfers in the form of books and piano lessons).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our model, similarly, a parent may find it optimal to restrict the choice set of the next member of the dynasty. Other related papers in this literature include Amador, Werning, and Angeletos (2006) and Bhatt and Ogaki (2012). Pavoni and Yazici (2016) studied an optimal taxation problem where the inefficiency in decision making that arises from time-inconsistent preferences calls for a positive tax on parental transfers.…”
Section: Related Literaturementioning
confidence: 99%